Plastic recycling and their use as raw material for the synthesis of carbonaceous materials - Meneses, Rodrigo Arbey Muñoz (2022)
Pollution by polymeric materials - in particular plastics - has a negative effect on the health of our planet. Approximately 4.9 billion tons of plastic are estimated to have been improperly disposed of, with the environment as their final destination. This scenario comes from a linear economic system, extraction-production-consumption and finally disposal. The alarming panorama has created the need to find technological solutions that generate new uses for discarded polymeric materials or turn them into part of the production process to produce new and novel materials, such as carbon nanotubes, graphene, or other carbonaceous materials of high added value, modifying the economy for a circular and sustainable production model. This review highlights the negative impact that the disposal of plastic materials has on the environment and the research needs that allow solving the pollution problems generated in the environment by these wastes. Also, the review highlights the current and future directions of recovery plastic waste research-based to promote innovations in the plastic production sector that could allow obtaining breakpoints in other industrial sectors with the technology-based companies.